Mathematics
Dong
45

The work of a student trying to solve the equation 3(4x − 2) = 9 + 2x + 5 is shown below: Step 1: 3(4x − 2) = 9 + 2x + 5 Step 2: 12x − 2 = 14 + 2x Step 3: 12x − 2x = 14 + 2 Step 4: 10x = 16 Step 5: x = 1.6 In which step did the student first make an error and what is the correct step?

+4
(1) Answers
Rolandoboss

The error is in step 2 3*-2 =-6 when distributing  Here is how to solve it correctly 3(4x − 2) = 9 + 2x + 5 12x-6=14+2x  (add 6 to both sides of the equations, the -6 gets canceled out) 12x=20+2x  10x=20  x=2 

Add answer